Communicative Competence Enhancement in Teaching Students with Special Needs - Alua, Smanova; Leskul, Ibraimova; Elmira, Aitenova; Raigul, Rakhmetova; Gaisha, Serikbayeva; Aidos, Abdykadyrov (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
Communication is powerful instruments of interaction that provide equality to those who have a severe intellectual disability. We are presenting a comprehensive communication model to enhance their chances of interacting with others and improving professionals’ understanding of intellectual disability. Most of the existing literature on different disabilities focuses on people who have some capacities to perform certain skills to a certain degree. Our model allows effective learning and proactive interaction for both the disabled and the professionals. Moreover, it offers resources and a wide range of knowledge about the syndromes and the right strategies to be used. The idea of this research paper arose out of an awareness that students with language learning disabilities are completely ignored in the educational system, and there are no special programs that cater to these students. They are placed in normal schools that are not prepared to deal with their unique difficulties. This paper, therefore, is an attempt to provide teachers with multiple-strategies models for teaching English language skills to these students at the intermediate level and beyond. Also, this research paper describes strategies for language learning and language use in regular language activities. Communication is powerful instruments of interaction that provide equality to those who have a severe intellectual disability. We are presenting a comprehensive communication model to enhance their chances of interacting with others and improving professionals’ understanding of intellectual disability. Most of the existing literature on different disabilities focuses on people who have some capacities to perform certain skills to a certain degree. Our model allows effective learning and proactive interaction for both the disabled and the professionals. Moreover, it offers resources and a wide range of knowledge about the syndromes and the right strategies to be used. The idea of this research paper arose out of an awareness that students with language learning disabilities are completely ignored in the educational system, and there are no special programs that cater to these students. They are placed in normal schools that are not prepared to deal with their unique difficulties. This paper, therefore, is an attempt to provide teachers with multiple-strategies models for teaching English language skills to these students at the intermediate level and beyond. Also, this research paper describes strategies for language learning and language use in regular language activities.